Reductive Coupling of Aromatic Aldehydes and Acetophenone Induced by TiCl4-Al/CH2(COOEt)2 - Song, Chang-Ying; Wang, Shu-Xiang; Chu, Wen-Hao; Li, Ji-Tai; Zhou, Zheng; Li, Hong-Yu; Cao, Zi-Qing (Asian Journal of Chemistry, 2013)
Induced by TiCl4-Al/CH2(COOEt)2 in CH2Cl2, some aromatic aldehydes and acetophenone can afford the corresponding 1,2-diols in 13-91 % yields with good dl-diastereoselectivities within 45-60 min at room temperature.